2016
DOI: 10.4162/nrp.2016.10.1.108
|View full text |Cite
|
Sign up to set email alerts
|

Consumer perceptions on sustainable practices implemented in foodservice organizations in Korea

Abstract: BACKGROUND/OBJECTIVESSustainable practices in foodservice organizations including commercial and noncommercial ones are critical to ensure the protection of the environment for the future. With the rapid growth of the foodservice industry, wiser usage of input sources such as food, utilities, and single use packaging should be reconsidered for future generations. Therefore, this study aims to investigate the customer's perceptions on sustainable practices and to identify the relationship among sustainable prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…As a long-term objective, improved competitiveness may manifest by increased customer loyalty, new customers, and an enhanced image and reputation of the organisation (de Burgos Jimenez et al, 2013). Ju and Chang (2016) suggest that sustainability practices present a good image to customers and increase the awareness of valuable contributions that benefit the customer as well as the community. Jay et al (2017) found that the enterprises, which had adopted social and environment practices, noted low levels of financial volatility, high levels of growth and higher rate of survival over a 15-year period.…”
Section: Sustainable Competitivenessmentioning
confidence: 99%
“…As a long-term objective, improved competitiveness may manifest by increased customer loyalty, new customers, and an enhanced image and reputation of the organisation (de Burgos Jimenez et al, 2013). Ju and Chang (2016) suggest that sustainability practices present a good image to customers and increase the awareness of valuable contributions that benefit the customer as well as the community. Jay et al (2017) found that the enterprises, which had adopted social and environment practices, noted low levels of financial volatility, high levels of growth and higher rate of survival over a 15-year period.…”
Section: Sustainable Competitivenessmentioning
confidence: 99%
“…These include using the SERVQUAL or the DINESERV model [68,69]. They can also be dedicated methods [63,[70][71][72][73]. The questionnaire was designed based on literature and previous research [68,69] and was validated by means of a pilot study with 20 people.…”
Section: Questionnaire Researchmentioning
confidence: 99%
“…Several studies focused on sustainability practices from the owner's or management's perspective, as well as focused on green restaurants or hotels in different countries [54][55][56][57][58][59]. There are a few studies [60][61][62][63][64] about sustainability practices in restaurants from the viewpoint of consumers of green restaurants, that are specific. There is little or no research from the viewpoint of consumers of common restaurants.…”
Section: Introductionmentioning
confidence: 99%
“…Especially for small start-ups, making effective use of online reviews could increase the chances of being discovered and gain a sustainable competitive advantage. However, it is important to note that sustainable aspects of a restaurant (e.g., green packaging, waste management, preservation of energy, and public relations on green activity) identified by Ju and Chang [82] are not emerged as a frequently-mentioned aspect. The potential reason might be that many of U.S. customers are unable to define green restaurant, even though they have eaten in a green restaurant [83].…”
Section: Implications Limitations and Future Studiesmentioning
confidence: 99%